Impact of neuroanatomical alterations identified by advanced imaging on the diagnosis and management of schizophrenia: a systematic review of psychosocial interventions and pharmacological therapies - Hernández, Rebeca Rosas; Santiago, Luisana Darionara Maldonado De; Miranda, Dario Javier Caguate; Velasco, Melanie Betsabe Orellana; Maldonado, Juan David Alzate; Arroba, Dianna Mishell Loor; Diego, Saltos Hernández Milton (International Journal of Research in Medical Sciences, 2024)
We aim to systematically evaluate neuroanatomical alterations identified through advanced imaging on the diagnosis and management of schizophrenia. Neuroimaging advancements of magnetic resonance imaging (MRI), positron emission tomography (PET) and diffusion tensor imaging have made it possible to reveal in-depth structural and functional abnormalities such as reduced grey matter in the prefrontal cortex and hippocampus or ventricular enlargement and disrupted white matter tracts such as in schizophrenia case. Key symptoms such as disordered behaviour, hallucinations, and cognitive deficiencies are correlated with these alterations. Morphological features are also associated with neurotransmitter dysregulation specifically about dopamine and glutamate. The review also looks at pharmacological treatments like antipsychotics and psychosocial methods like cognitive behavioural therapy emphasising their varying effectiveness in treating the complex symptomatology of schizophrenia. Although there is potential for individualized treatment when neuroimaging results are integrated with clinical techniques but there are still obstacles to putting these insights into practice, especially in areas with low resources.